Extracorporeal Membrane Oxygenation Advances in Therapy - Firstenberg, Michael S. (IntechOpen, 2016)
Extracorporeal membrane oxygenation (ECMO), despite a long and troubled history, is very rapidly evolving into a therapy that can be safely and effectively applied across the world in patients experiencing acute cardiac and/or pulmonary failure. As experiences grow, there is a better understanding of nuances of the importance of teamwork, therapy guidelines and protocols, patient selection, and understanding the functional aspects of pump-circuit technology as it interfaces with human biology. The challenges in managing these very sick and complex patients cannot be understated. The goal of this text is to provide a framework for the development and successful growth of a program. Authors from Centers of Excellence Worldwide have shared their experiences in the full spectrum in dealing with this evolving field.